Pertumbuhan rumput laut (Kappaphycus alvarezii) yang dibudidaya dalam kantong jaring dengan berat awal berbeda di Teluk Talengen Kepulauan Sangihe - Sahabati, Susanty; Mudeng, Joppy D.; Mondoringin, Lukas L.J.J. (e-Journal BUDIDAYA PERAIRAN, 2016)
The research aimed to study the growth  of seaweed Kappaphycus alvarezii cultured for 42 days  (from May to June 2016) in net pen with different initial weights at Talengen Bay, Island of Sangihe, North Sulawesi Province. The research used Complete Randomized Design with three treatments, each with three replication. The treatments included A: 50 g, B: 100 g, and C: 150 g of initial weight. Data collected were absolute, relative and daily growth.  Data were analyzed using analysis of variance and Least Significance Different Test was used to determine the difference between treatments.  Statistical analysis used JMP (SAS-institute). Research results showed the best absolute growth was achieved in treatment C namely 300.55 g, the best relative growth was observed  in treatment A as much as 284.78% and the best daily growth rate was in treatment A as much as 3.26%. Keywords:  seaweed, net pen, absolut growth, relative growth, daily growth